Health service accessibility and deaths from asthma in 401 local authority districts in England and Wales, 1988-92. Issue 3 (March 1997) - Jones, A P; Bentham, G
Abstract : BACKGROUND: The possible contribution of health service accessibility to asthma mortality has not previously been studied in the UK. METHODS: Using regression analysis, the relationship between geographical isolation from large acute hospital services and mortality from asthma for 401 local authority districts in England and Wales was examined for the period 1988-92. RESULTS: Asthma mortality was found to be strongly associated with the proportion of district households where the head was of social class 4 or 5 (adjusted relative risk 1.61, 95% confidence interval (CI) 1.12 to 2.33), and the proportion of households without access to a car (adjusted relative risk 1.59, 95% CI 0.97 to 2.62). After controlling for these factors, there was a tendency for mortality to rise with increasing distance from hospital, with a relative risk of 1.01 for an increase in distance of one kilometre (95% CI 1.00 to 1.02). CONCLUSIONS: The findings suggest that problems of accessibility of care may mean that the control of asthma amongst sufferers living in districts most remote from major health service units might be less than optimal, and this could result in a number of potentially avoidable deaths.